Using eye tracking to identify cultural differences in information seeking behavior - Marcos, M; Garcia-Gavilanes, R; Bataineh, E; Pasarin, L (ACM SIGCHI, 2014)
The main goal of this research is to investigate how people with different cultural background differ in their interaction style and visual behavior on search engine results pages (SERP), more specifically between groups from the Middle Eastern region vs. Western Europe. The researchers conducted a controlled eye-tracking experiment to explore and evaluate the visual behavior of Arab (U.A.E) and Spaniard users when scanning through the first page of the search results in Google. Significant differences were observed in the 4 aspects of the study: U.A.E. participants stayed longer on the SERPs, read more search results and viewed each snippet in a more detailed way than their counterpart, Spaniards. In Spain, people tended to scan the SERP, reading less text on each snippet, and chose a result among the first top ranked ones without paying attention to those in the bottom positions.